Optical component reliability in high-energy laser systems: Challenges and insights - Mureșan, Mihai-George; Novák, František; Uvarova, Liliia; Vanda, Jan; Brajer, Jan; Mocek, Tomáš (EPJ Web of conferences, 2024)
The laser-induced damage resistance of large optical components remains an important limitation for the maintenance costs, reliability, and further development of high energy/high-power (HEL/HPL) laser systems. With numerous manufacturers providing different laser-induced damage threshold (LIDT) values in the nanosecond regime, a simple ranking based on numbers alone may not provide a clear picture of the best choice. Variations in testing procedures, albeit following the ISO 21254 standard, further complicate the selection process. By employing a comprehensive 1-on-1 test procedure, it becomes possible to observe various parameters that influence LIDT values. An overview on how the laser beam size, the spectral characteristics of the tested optic and possible contamination of the surface are influencing the LIDT values will be presented.